Leveling Up Language: The Impact of Gamified English Activities on Early Childhood Vocabulary and Phonological Awareness - Yusuf Hidayat (Nexus Publishing NXP, 2025)
Despite the growing interest in gamified approaches to early childhood English instruction, existing research often emphasizes engagement and enjoyment while providing limited evidence on their efficacy in fostering language-specific competencies such as vocabulary acquisition and phonological awareness. Addressing this gap, the present study aimed to examine the impact of gamified English activities on young learners’ vocabulary breadth and phonological skills. Employing a quasi-experimental research design, data were collected from 48 children aged 4–6 years enrolled in a private early childhood institution in West Java, Indonesia. Participants engaged in a structured gamified curriculum integrating interactive storytelling, digital games, and classroom-based phonics challenges over an eight-week period. Pre- and post-tests measured vocabulary knowledge and phonological awareness, while observational logs and teacher interviews provided qualitative insights. Results indicated that gamified activities enhanced children’s word retention, segmental awareness, and confidence in verbal expression, though variability was observed in the degree of improvement across participants, with some demonstrating slower adaptation to structured gamified tasks. Observational data also highlighted occasional over-reliance on game mechanics at the expense of deliberate practice, suggesting the need for carefully balanced scaffolding. These findings underscore both the potential and the limitations of gamification as an instructional and assessment tool in early English language development.